SIRT1 and p53, effect on cancer, senescence and beyond - Yi, Jingjie; Luo, Jianyuan (Biochimica et biophysica acta, 2010)
NAD +-dependent Class III histone deacetylase SIRT1 is a multiple function protein critically involved in stress responses, cellular metabolism and aging through deacetylating a variety of substrates including p53, forkhead-box transcription factors, PGC-1α, NF-κB, Ku70 and histones. The first discovered non-histone target of SIRT1, p53, is suggested to play a central role in SIRT1-mediated functions in tumorigenesis and senescence. SIRT1 was originally considered to be a potential tumor promoter since it negatively regulates the tumor suppressor p53 and other tumor suppressors. There is new evidence that SIRT1 acts as a tumor suppressor based on its role in negatively regulating β-catenin and survivin. This review provides an overview of current knowledge of SIRT1-p53 signaling and controversies regarding the functions of SIRT1 in tumorigenesis.